The extent of use of teaching methods of teacher training strategies of the Ministry of Education of the Kurdistan Regional Government from the perspective of high school students and their orientation towards teaching lessons and teaching methods - محمد, م.سەربەست کریم محمد; علی, م.م. لانە لطیف علی (Sulaimani Journal for Humanities, 2025)
The aim of this research was to identify: (the level of using Teachers training strategy teaching methods in various subjects and preparatory schools, students’ attitudes towards their academic subjects, the role of these methods in shaping students’ attitudes towards learning academic subjects, and students’ attitudes towards using these methods across all Teachers training strategies) in the governorate of Sulaimani from the perspective of students.This project is currently being implemented in primary schools and preparatory schools across all districts at the same time, on a topic assigned by the Ministry of Education, in which teachers are being trained by teachers trainer.The research followed a descriptive–survey comparative approach. A questionnaire was prepared by the researchers, consisting of three forms with a total of )21( items. The research population consisted of morning preparatory schools under the administration of the Directorate of Education in Western Sulaimani, with a total of )60( preparatory schools (excluding evening schools). The research sample was selected randomly )11( preparatory schools, and from each school, one 10th-grade science class was selected to participate in the survey, totaling )218( students.The methods of mind map and concept map recorded the highest usage rates across all preparatory schools. Students’ attitudes showed greater interest and enjoyment in learning subjects such as (Islamic Education, Biology, English, and Chemistry) compared to subjects such as( Physics, Arabic, Kurdish, and Mathematics). The use of teachers training strategy teaching methods by teachers increased students’ interest and enjoyment in their subjects. Students’ attitudes towards using methods within instructional strategies were higher than their attitudes towards purely lecture-based methods. Moreover, the methods introduced to teachers during early-year training sessions were more frequently used in classrooms and subjects.
Keywords: Teachers training strategies; Students attitudes towards academic subjects; Students attitudes towards Teachers training strategy methods; Students Affection for lessons; Students Enjoyment of learning